An Analysis of the Students’ Anxiety in English Speaking Course at Universitas Qomaruddin - Khoirul Anwar; Eva Nur Mazidah (ELITE Association Indonesia, 2023)
This research focuses on analyzing the types, factors and level of students’ anxiety in English speaking course. The participant of this research was 27 students from the fourth semester of English Language Education Program, Faculty of Teacher Training and Education Universitas Qomaruddin in 2021/2022 academic year. This research used three instruments namely observation checklist, questionnaire sheet and interview guidelines. This researcher used FLACS questionnaire as its main instrument to identify the cause and the level of students’ anxiety in speaking English. Whereby, an observation had done by the researcher for three times to validate the behavior and the problems experienced by the participant. To collect more information about the anxiety did by the participants, an interview section was held by the researcher. The researcher used purposive sampling and chose 8 participants based on their anxiety score. Based on the calculated data done by the researcher on observation sheet, it showed that the category of students’ level of anxiety was on moderate level with the total score 1956 and its average (mean) was 72,44; the types of students’ anxiety were communicative apprehension, test anxiety and fear of negative evaluation in which students showed wrong attribution of body signal, lack of vocabulary, low English proficiency, over self-prediction toward fear, over sensitivity toward threat, irrational faith and lack of preparation which became the factors caused students’ anxiety. Their way to overcome their anxiety were to make a good preparation, to try to relax, to think positive, to have peer seeking, and to withdraw. Keywords: students’ anxiety, speaking